2020
DOI: 10.1111/jcmm.15207
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor 5 blockade modulates macrophage trafficking in renal ischaemic‐reperfusion injury

Abstract: Chemokine receptor 5 (CCR5) is a pivotal regulator of macrophage trafficking in the kidneys in response to an inflammatory cascade. We investigated the role of CCR5 in experimental ischaemic‐reperfusion injury (IRI) pathogenesis. To establish IRI, we clamped the bilateral renal artery pedicle for 30 min and then reperfused the kidney. We performed adoptive transfer of lipopolysaccharide (LPS)‐treated RAW 264.7 macrophages following macrophage depletion in mice. B6.CCR5−/− mice showed less severe IRI based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Male C57BL/6 (B6) mice (aged 8 weeks) were procured from the Orient Company (Seoul, Republic of Korea) and housed in a pathogen‐free animal facility. Renal ischemia–reperfusion injury (IRI) was induced unilaterally and bilaterally following previously established experimental protocols 19–24 . Prior to the procedure, wild‐type mice were anesthetized via an intraperitoneal injection using an anesthetic solution of tiletamine mixed with zolazepam (1:1) (Zoletil; 30 mg/kg of body weight; Virbac, USA) and xylazine (25 mg/mL) (Rompun; 10 mg/kg of body weight; Bayer, Canada) 25 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male C57BL/6 (B6) mice (aged 8 weeks) were procured from the Orient Company (Seoul, Republic of Korea) and housed in a pathogen‐free animal facility. Renal ischemia–reperfusion injury (IRI) was induced unilaterally and bilaterally following previously established experimental protocols 19–24 . Prior to the procedure, wild‐type mice were anesthetized via an intraperitoneal injection using an anesthetic solution of tiletamine mixed with zolazepam (1:1) (Zoletil; 30 mg/kg of body weight; Virbac, USA) and xylazine (25 mg/mL) (Rompun; 10 mg/kg of body weight; Bayer, Canada) 25 .…”
Section: Methodsmentioning
confidence: 99%
“…25 Subsequently, bilateral flank incisions were performed, and both renal pedicles were carefully dissected and clamped using a microvascular clamp (Roboz Surgical Instrument, Gaithersburg, MD, USA) for 30 min. 19,20,23,26 Throughout the procedure, 2 mL of sterile saline at 40°C (1 mL during ischemia and 1 mL during reperfusion) was administered into the peritoneal cavity. Body temperatures were consistently monitored and maintained at 37°C during the renal IRI process.…”
Section: Experimental Animals For Acute Kidney Injury and Acute Kidne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine receptor 5 (CCR5) is a pivotal regulator of the inflammatory cascade response of macrophages in the kidney, and its deficiency contributes to the activation of M2 macrophages ( Fig. 2 ; Table I ) ( 109 ). Therefore, blocking CCR5 may be helpful in the treatment of I/R-AKI.…”
Section: Macrophage-sensing Mediators In Akimentioning
confidence: 99%
“…They play an essential role in leukocyte migration ( Kufareva et al, 2015 ). Recent studies showed that CXCR family is highly involved in kidney diseases ( Ye et al, 2018 ; Yahong Liu et al, 2020 ; Yoo et al, 2020 ). In our previous study, we have found that CXCR4 promotes tubular injury and renal fibrosis through activating β-catenin ( Mo et al, 2017 ; Yahong Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%